2008
DOI: 10.1021/es703199g
|View full text |Cite
|
Sign up to set email alerts
|

Indirect Evidence of Transposon-Mediated Selection of Antibiotic Resistance Genes in Aquatic Systems at Low-Level Oxytetracycline Exposures

Abstract: Subinhibitory levels of antibiotics can promote the development of antibiotic resistance in bacteria. However, it is unclear whether antibiotic concentrations released into aquatic systems exert adequate pressure to select populations with resistance traits. To examine this issue, 15 mesocosms containing pristine surface water were treated with oxytetracycline (OTC) for 56 days at five levels (0, 5, 20, 50, and 250 microg L(-1)), and six tetracycline-resistance genes (tet(B), tet(L), tet(M), ted(O), tet(Q), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
68
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(72 citation statements)
references
References 41 publications
2
68
0
Order By: Relevance
“…However, a previous study demonstrated that low concentrations of antibiotics could also induce ARGs and/ or stimulates horizontal gene transfer of ARGs (Storteboom et al, 2010). Subinhibitory concentrations of oxytetracycline as low as 20 mg L À1 were able to select for tetracycline resistance, as shown by an increasing ratio of tet over 16S rRNA gene in surface water mesocosms (Knapp et al, 2008). It was found that the patterns of antibiotics distribution among different parks were different, including parks using reclaimed water from the same WWTPs (Table S1 and Fig.…”
Section: Antibiotics Concentrationsmentioning
confidence: 96%
“…However, a previous study demonstrated that low concentrations of antibiotics could also induce ARGs and/ or stimulates horizontal gene transfer of ARGs (Storteboom et al, 2010). Subinhibitory concentrations of oxytetracycline as low as 20 mg L À1 were able to select for tetracycline resistance, as shown by an increasing ratio of tet over 16S rRNA gene in surface water mesocosms (Knapp et al, 2008). It was found that the patterns of antibiotics distribution among different parks were different, including parks using reclaimed water from the same WWTPs (Table S1 and Fig.…”
Section: Antibiotics Concentrationsmentioning
confidence: 96%
“…Singleplex qPCR using SYBR green detection has previously been used to detect certain antibiotic resistance genes in environmental samples, most frequently identified in water or waste water samples (Volkmann et al, 2004(Volkmann et al, , 2007Borjesson et al, 2009;Knapp et al, 2008;Koike et al, 2007;Pruden et al, 2006;Smith et al, 2004). The SYBR Green RT-PCR chemistry may generate false positive results as it binds to any double-stranded DNA, and as such can also bind to non-specific double-stranded DNA sequences.…”
Section: Discussionmentioning
confidence: 99%
“…For sulfadiazine, concentrations of 150 µg kg -1 in soil were shown to have a selective effect on the resistant population . Increased selection for tetracycline resistant genes was also apparent at exposures as low as 20 μg L -1 OTC in surface water mesocosms (Knapp, 2008). Interestingly, a recent study suggests that the manure itself could be contributing to resistance, apparently by selectively supporting the growth of beta lactam resistant bacteria, although the exact mechanism is unknown (Udikovic-Kolica, 2014).…”
Section: Effects On Antimicrobial Resistancementioning
confidence: 99%